Rise and decline of the clay factory: Reverse weathering and C-Si coupling across the Ediacaran-Cambrian transition - Qianmin Yang; Zengrun Yang; Mu Liu; Guodong Liu; Tianshun Wang; Gan Luo; Li Yang; Shuhang Chen; Muhuan Luo; Meiqiu Zhou; Zhangqing Yan; Yong Fu (Science China Earth Sciences, 2026)

Carnitine acetyltransferase acts as a unidirectional compensatory enzyme for choline acetyltransferase activity in Nilaparvata lugens - Zhen Zhang; Jingting Wang; Tianshun He; Tianye Hu; Xun Wu; Huihui Zhang; Na Yu; Zewen Liu (Pesticide Biochemistry and Physiology, 2026)

Prototypical basin reconstruction and evolutionary models for the Precambrian of the Qinshui Basin, North China craton - Tianshun Liu; Wenlong Ding; Zhong Liu; Zhijun Li; Pengbao Zhang; Chuanli Peng; Xiaoyun Cheng; Tingfeng Liu; Tong Gou (Marine and Petroleum Geology, 2024)

The down-regulation of salivary protein gene expression by etofenprox partially contributed to reducing the risk of increased fecundity in the brown planthopper - Haoli Gao; Xiaowei Yuan; Tianshun He; Zhen Zhang; Jingting Wang; Huihui Zhang; Xumin Lin; Zewen Liu (Pesticide Biochemistry and Physiology, 2024)

The method and application of numerical simulation of high-precision stress field and quantitative prediction of multiperiod fracture in carbonate reservoir - Pengyuan Han; Wenlong Ding; Hailong Ma; Debin Yang; Jing Lv; Yuntao Li; Tianshun Liu (Tectonophysics, 2024)

Genesis of Danping bauxite (Northern Guizhou, China) and associated lithium: Evidence from LA-ICP-MS analysis of Al-bearing minerals - Bing Liu; Peiwen Chen; Tianshun Wang; Guotao Sun; Mingfei Duan; Kejun Hou; Qingdong Zeng; Yong Fu (Journal of Geochemical Exploration, 2024)

Local pH regulation at zinc vanadate cathode by a hierarchical structure for long-life aqueous zinc batteries - Tianshun He; Ruoyao Wang; Hua-Yu Shi; Xiao-Xia Liu; Xiaoqi Sun (Chemical Engineering Journal, 2024)

Numerical analysis of hydrological response in loess excavation and filling area under multi-year precipitation infiltration - Tianshun Wang; Fei Liu; Yongtang Yu; Huaien Cai (Bulletin of Engineering Geology and the Environment, 2023)

Cenozoic tectonostratigraphy and structural styles in the Nangong Sag, Bohai Bay Basin, eastern China: Implications for the generation of oil-gas traps - Tianshun Liu; Wenlong Ding; Ruifeng Zhang; Jingtian Li; Guangye Feng; Pengyuan Han; Xu Zhou; Dashuai Ye; Ziyou Zhang (Marine and Petroleum Geology, 2023)

Hydrogelation of TPGS for locoregional combination therapy of cancer - Yao Xiong; Tianshun Wang; Lei Liu; Yuanqi Kou; Zhengyu Zhao; Min Yuan; Yan Chen; Dan Wang; Shiyong Song (Chemical Engineering Journal, 2023)

How does turions production of Potamogeton crispus L. respond to parental population biomass and living environment - Tianshun Zhu; Lihong Wang; Xin Ding; Zihao Wen; Liang He; Jing Chen; Yang Yang; Zugen Liu; Jianfeng Chen; Meng Zhang (Environmental Science and Pollution Research, 2022)

Structural styles and tectonic evolution of Cretaceous to Cenozoic faults in the Linhe Depression of Hetao Basin, China: implications for petroleum traps - Zhicheng Zhou; Wenlong Ding; Ruifeng Zhang; Danping Yan; Baocheng Jiao; Chenlin Wu; Tianshun Liu; Xiaoyu Du; Mingwang Xue (International Journal of Earth Sciences, 2021)

Phosphorus availability increases pathobiome abundance and invasion of rhizosphere microbial networks by Ralstonia - Pengfa Li; Ming Liu; Guilong Li; Kai Liu; Tianshun Liu; Meng Wu; Muhammad Saleem; Zhongpei Li (Environmental Microbiology, 2021)
Summary Soil disease‐suppressiveness depends on complex interactions among pathogens, native microbiota, and physicochemical properties, while these interactions remain understudied. Comparing field and microcosm experiments, we investigated the significance of these interactions in disease emergence or suppression using structural equation modelling (SEM) and receiver operating characteristic curve (ROC) analyses. We observed significant differences in the relative abundance of pathogenic and beneficial microbes, alpha and beta diversity indices between disease‐conducive and ‐suppressive rhizosphere soils. The pathogenic ( Ralstonia ) and beneficial ( Bacillus ) taxa dominated disease‐conducive and ‐suppressive rhizosphere soils, respectively. Moreover, the co‐occurrences of Ralstonia with native microorganisms were positive and negative in the disease‐conducive and ‐suppressive soils, respectively. These results suggest the supportive ( Rudaea ) and suppressive ( Enterobacter , Bacillus ) role of indigenous microbes in the invasion of soil and plant systems by Ralstonia . The SEM and ROC analysis predicted that Ralstonia invaded rhizospheric microbial networks and caused peanut wilt under high than low soil phosphorus conditions. Our results suggest the importance of soil phosphorus availability in altering the microbial interactions, thus leading to soil invasion by Ralstonia . Thus, we conclude by saying that feeding soil with high amounts of available phosphorus could deplete plant‐beneficial microbes and increase the pathobiome abundance that may compromise plant health.

The interannual and decadal variability of the sea level in the Japan/East Sea - Tianshun Wang; Yuguang Liu; Haibo Zong; Zengrui Rong (Journal of Ocean University of China, 2009)